Towards a G20 Strategy for Promoting Inclusive Global Value Chains - OECD; World Bank Group; International Trade Centre (World Bank, Washington, DC, 2016)
The paper draws on the Inclusive Global Value Chains report submitted by the OECD and the World Bank Group to G20 Trade Ministers in October 2015, refining and prioritizing the options contained therein. The original report proposed a holistic approach to promoting more inclusive Global Value Chains (GVCs) spanning: (i) trade, investment and domestic policies both in G20 nations and in trade partner countries; (ii) investment in expanding the statistical basis and technical analysis of participation in GVCs; and (iii) sharing knowledge on best practices on rules, policies and programs . This paper also takes into account relevant policy documents published since October 2015, including insights obtained from recently published reports on Aid for Trade.